The Effect of Eco-Enzyme Spraying on Suwung Landfill Waste, Denpasar, on Changes in Leachate Characteristics - I Nengah Muliarta; I Dewa Nyoman Sudita; Yohanes Parlindungan Situmeang (JURNAL KESEHATAN LINGKUNGAN, 2023)
Introduction: Bali, as an international tourist destination, is still experiencing problems in waste management. Suwung Landfill, Denpasar, is one of the landfills for waste originating from the Denpasar, Badung, Gianyar, and Tabanan (Sarbagita) areas. Methods: This research was an experimental study, by watering eco-enzymes on garbage heaps and examining changes in leachate parameters. Watering was carried out daily at a dose of 1 L of eco-enzyme dissolved in 1000 L of water and used for watering a garbage pile of 1 ha. The area of piles of garbage watered with eco-enzymes reaches 5 ha. Measured leachate parameters include pH, BOD, COD, TSS, N, cadmium, and mercury. Results and Discussion: Eco-enzymes have the potential to become activators or decomposers in waste composting. The evidence is that eco-enzyme watering causes the average leachate temperature to range from 36.63 to 40.370C, where the increase in leachate temperature occurs due to the rise in the temperature of the garbage pile. An increase in temperature characterizes the activity of microbes increases, so the decomposition process becomes rapid. Conclusion: Eco-enzyme spraying leads to a characteristic change in the form of an increase in the value of leachate parameters. The increase in temperature value, pH, BOD, COD, and N content of leachate indicates that environmentally friendly enzymes accelerate the decomposition of organic matter. The rapid decomposition process causes the total suspended density of leachate to increase.